A virtual roundtable on Iser’s legacy Part III: a conversation with Marco Caracciolo (ENTHYMEMA, 2017)
In this article you find the third part of a roundtable on Wolfgang’s Iser legacy with Gerald Prince, Mark Freeman, Marco Caracciolo and Federico Bertoni. In Part III we discuss with Marco Caracciolo the common grounds of Iser and cognitive literary approaches and the role of interpration in cognitive literary studies.